Mergers and Acquisitions Current Issues - Gregoriou, G.; Neuhauser, Karyn; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2007)
This collection of exclusive articles presents the latest research in the area of mergers and acquisitions. It presents what drives corporate performance under different economic conditions, both in the US and across the globe, and examines the role of mergers and acquisitions in maintaining the efficiency of world markets.
Keywords: Accounting; Bookkeeping .; International business enterprises; Organization; Planning; Accounting/Auditing.; International Business; Organization